4. Didactic Challenges in Teaching Violin Skills, at the Level of Beginner Pupils - Stanciu Alina (Sciendo, 2023)
The supporting idea of this work is to facilitate the acquisition and education of some violinist skills at the level of beginner pupils, using their little musical "creations". The experimental study was implemented by the practicing students, within the activities of the "Pedagogical Practice" discipline.